Conditions and Factors of the Positive Investment Climate Formation of Social and Economic System of the Region - Litvinenko, Inna L.; Grabar, Anna A.; Tikhomirov, Evgeny A.; Tupchienko, Vitaly A.; Yudenkov, Yuri N.; Gabidullina, Chulpan F. (International Review of Management and Marketing, 2016)
The article deals with two positions conditions and factors creating a positive investment climate of the region socio-economic system. Authors in two directions present the investment structure: financial investments and intellectual investments into regional socio-economic system of the Krasnodar Territory. According to the World Bank data on the total index of the economy competitiveness (380 indicators, including the research and development level), the Russian Federation took place in 1994 the fourth top ten place among the 180 countries of the world. In the ten-plus years, our country has moved into the second hundred. In the USSR in 1991, 190 thousand applications for inventions were filed. Now this figure decreased to 22 thousand. According to SRI FRCEC only 5-6% of Russian industrial companies are developing and introducing technological innovations. In the late 80-ies, such companies were 60-70%. Innovative products in the Russian Federation today, and not gaining 1%, the same figure in Finland – more than 30%, in Italy, Portugal and Spain – from 10% to 20%. The share of Russia in world trade in civil high-tech products for a number of years does not exceed 0.3 – 0.5%. For comparison, the US share – 36%, Japan – 30%, Germany – 17%, China – 6%. Keywords: investment attractiveness, intensification, investment climate, the region economic system JEL Classifications: G11, G18, R11, R58